2018
DOI: 10.1016/j.foodchem.2017.07.047
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different hydrocolloids on dough thermo-mechanical properties and in vitro starch digestibility of gluten-free steamed bread based on potato flour

Abstract: Please cite this article as: Liu, X., Mu, T., Sun, H., Zhang, M., Chen, J., Fauconnier, M.L., Influence of different hydrocolloids on dough thermo-mechanical properties and in vitro starch digestibility of gluten-free steamed bread based on potato flour, Food Chemistry (2017), doi: http://dx.doi.org/10.1016/j.foodchem. 2017.07.047 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
93
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(101 citation statements)
references
References 39 publications
7
93
0
1
Order By: Relevance
“…HPMC as the most widely used hydrocolloid seems logical considering that this hydrocolloid yields breads with higher volume (Sabanis & Tzia, 2011). It also seems logical that HPMC is commonly mixed with other hydrocolloid sources, based on the drier and more crumbly texture of HPMC breads (Liu et al, 2018). In fact, locust bean, guar, or xanthan gums have a greater water holding capacity than HPMC (Horstmann, Axel, & Arendt, 2018), which can help reduce the crumbly texture and dryness.…”
Section: Ingredientsmentioning
confidence: 99%
“…HPMC as the most widely used hydrocolloid seems logical considering that this hydrocolloid yields breads with higher volume (Sabanis & Tzia, 2011). It also seems logical that HPMC is commonly mixed with other hydrocolloid sources, based on the drier and more crumbly texture of HPMC breads (Liu et al, 2018). In fact, locust bean, guar, or xanthan gums have a greater water holding capacity than HPMC (Horstmann, Axel, & Arendt, 2018), which can help reduce the crumbly texture and dryness.…”
Section: Ingredientsmentioning
confidence: 99%
“…Amritpal et al [76] found that the addition of xanthan and guar gum improved peak viscosity, hot-paste viscosity and final viscosity for mung and corn starches; while for potato starch, guar gum increased peak and final viscosities and decreased hot paste viscosity while xanthan gum increased hot-pasteand final viscosities and decreased peak viscosity. All those results about the functional properties of hydrocolloids concluded that a unique trend did not exist and the impact of hydrocolloids on dough thermo-mechanical properties greatly depend on the nature of the flour components, the chemical structure of specific hydrocolloid and the quantity of added hydrocolloids [75].…”
Section: Hydrocolloidmentioning
confidence: 99%
“…It has been reported that the hydration property of wheat flour-hydrocolloids mixtures was greatly increased due to the high affinity of hydrocolloids to water, which would affect the dough-rheological properties and food quality significantly [75]. Rosell et al [72] investigated the effect of four widely used hydrocolloids, including sodium alginate, k-carrageenan, xanthan gum and HPMC, on the rheological properties of the wheat flour dough.…”
Section: Hydrocolloidmentioning
confidence: 99%
See 2 more Smart Citations